Low-dose administration of prednisone has a good effect on the treatment of prolonged hematologic toxicity post-CD19 CAR-T cell therapy - Wang, Jiaxi; Zhang, Meng; Lyu, Hairong; Guo, Ruiting; Xiao, Xia; Bai, Xue; Pu, Yedi; Meng, Juanxia; Li, Qing; Yuan, Ting; Lu, Wenyi; Zhao, Mingfeng (Frontiers in Immunology, 2023)
Abstract Hematologic toxicity (HT) is a joint adverse event after CAR-T cells infusion. Some patients experience prolonged hematologic toxicity (PHT), which is challenging to treat. Among 109 patients with relapsed refractory B-ALL treated with CD19 CAR-T cells at Tianjin First Central Hospital, 78.9% (86/109) of patients were evaluated as PHT. Of these, 15 patients did not respond to erythropoietin, platelet receptor agonists, transfusion or G-CSF (12 were grade 3/4 cytopenia, 12 were trilineage cytopenia and 3 were bilineage cytopenia), 2 developed cytopenia without apparent cause after D28. They eventually treaded with oral low-dose prednisone. We retrospectively analyzed the efficacy and safety of low-dose prednisone on PHT. The initial prednisone dose was 0.5 mg/kg/day, and the median response time was 21 days (7-40 days). The recovery rate of blood count was 100%, and the complete recovery rate ranged from 60% to 66.67%. Especially exciting was that HT recurred in 6 patients after stopping prednisone. They were relieved again after the administration of prednisone. The median follow-up time was 14.97 months (4.1-31.2 months). Twelve-month duration of PFS and OS rates were 58.8% (±11.9%) and 64.7% (±11.6%). We did not observe any other side effects of prednisone apart from drug-controllable hyperglycemia and hypertension. Therefore, low-dose prednisone is a beneficial and tolerable therapy for PHT after CAR-T cells. The trials have been registered at www.chictr.org.cn as ChiCTR-ONN-16009862 (November 14, 2016) and ChiCTR1800015164 (March 11, 2018).